The Contribution of SME to Regional Economic Development: On example of Adjara Autonomous Republic - Glonti, Vladimer; Manvelidze, Rezo; Surmanidze, Iamze (European Journal of Sustainable Development, 2021)
Small and medium entrepreneurship (SME) is one of the most important sectors of the national economy. It determines the economic growth rate of the country/region and the structure of the gross national product. The article aims at evaluating the contribution of SME to the regional economic development on example Adjara A.R. (Republic of Georgia), investigating and analyzing importance of SME development at regional level and discussing the factors influence on its development. In the research section of the given article econometric analyses of SME key indicators is conducted by linear log-regression model based on statistical data of 2006-2019 years. The results of the research study show positive impacts of the number of employees and their productivity on gross value added. The study aims at underlining the government policy supporting an advantageous SME environment and conditions, which is a precondition for regional economic development.